THE SUSTAINABILITY LIVING LAB PROGRAM: NETWORK FOR LOCAL UNIVERSITIES - Yermekova, Gulzhan (Nazarbayev University, 2023)
1. Campus environmental performance 2. Education for Sustainable Development 3. Research for Sustainable Development 4. Building national sustainability network among local universities and institutions 5. Participation in international networks 6. Contribution to the City resilience and State’s response to Climate Change
Keywords: Type of access: Open Access; Sustainability Development; Climate change